1991
DOI: 10.1007/bf00224984
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of the wild incompatibility alleles of the tetrapolar basidiomycete Agrocybe aegerita

Abstract: The variability of the sexual incompatibility genes of Agrocybe aegerita was investigated in the homokaryotic progeny of 13 wild dikaryotic strains from five distinct European geographic origins. Results of mating tests allowed identification of 18 A alleles and 16 B alleles out of a possible 26 different alleles for each in the sample. The determination and the comparison by a contingency χ (2) test of the frequencies of allele replications between intra- and interregional matings showed no departure from a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, Raper et al (1958) showed that pairs of fungal isolates collected from geographically distant collections were as likely to share alleles at a mating locus as pairs taken from the same locale. The mating allele distributions of several other mushroom species, such as Sistotrema brinkmannii (Ullrich and Raper 1974), Fomes cajanderi (Neuhauser and Gilbertson 1971), Pleurotus pulmonarius (Bresinsky et al 1987), Agrocybe aegerita (Noel et al 1991), and Panellus stypticus (Peterson and Bermudes 1992), have similarly demonstrated no apparent correlation with geography or climate. The major conclusion from these analyses of mating factors is that long distance gene flow is commonplace, and that these broadly distributed species may even be panmictic over their geographic range.…”
mentioning
confidence: 99%
“…In addition, Raper et al (1958) showed that pairs of fungal isolates collected from geographically distant collections were as likely to share alleles at a mating locus as pairs taken from the same locale. The mating allele distributions of several other mushroom species, such as Sistotrema brinkmannii (Ullrich and Raper 1974), Fomes cajanderi (Neuhauser and Gilbertson 1971), Pleurotus pulmonarius (Bresinsky et al 1987), Agrocybe aegerita (Noel et al 1991), and Panellus stypticus (Peterson and Bermudes 1992), have similarly demonstrated no apparent correlation with geography or climate. The major conclusion from these analyses of mating factors is that long distance gene flow is commonplace, and that these broadly distributed species may even be panmictic over their geographic range.…”
mentioning
confidence: 99%
“…Dikaryotic mycelia were cultivated in vitro to obtain basidiocarps from which basidiospores, which germinated to produce homokaryotic progeny, were isolated (10). Mating type alleles were identified as previously described (19).…”
Section: Methodsmentioning
confidence: 99%
“…The wild dikaryotic strains used, SM47 (mating-type alleles: A7A8 B4BQ and SM51 (A3A4 B3B4), were derived from in vitro cultures of fragments of fruiting bodies collected from nature. The dikaryotic strain SM47 was cultivated in vitro to obtain basidiocarps from which homokaryotic progeny A1 was obtained (Noel et al, 1991). The two strains SM51 and A1 were shown to lack dsRNA molecules and, accordingly, were used as controls in the RNA polymerase assays.…”
Section: Methodsmentioning
confidence: 99%